Impact of resistant vs. digested starch on starch energy value in the pig gut. (July 2018) - Fouhse, Janelle M.; Zijlstra, Ruurd T.
Abstract: A major energy substrate for monogastric species such as humans and swine is starch from cereal grains, pulses and tubers. The rate, site and extent of starch digestion in the gastro-intestinal tract are dependent on the intrinsic factors of starch origin and the extrinsic factors such as applied processing methods. In monogastric species, starch escaping small intestinal digestion becomes readily available for microbial fermentation in the hindgut and has been coined resistant starch (RS) accordingly. Host physiological and metabolic responses differ according to the site and rate of starch digestion; however, the quantity of energy derived to the host from fermented vs. digested starch remains debated. A detailed understanding of the underlying mechanisms that cause nutrient flow and substrate availability in the hindgut to alter host energy metabolism and growth potential is lacking. Dietary RS may in fact have nearly equal energetic efficiency as digested starch due adequate provision of short chain fatty acids (SCFAs) and decreased energy loss due to decreased activity. Thus, proper characterization of the energetic efficiency of purified and whole grain starch sources is required for accurate diet formulation. This review will focus on how various methodologies can be used to quantify site, extent and kinetics of starch digestion, illustrating the differences in energetic efficiency between RS vs. digested starch.